Work-energy pathway analysis of boundary layer ingestion in propulsive fuselage aircraft - Moirou, Nicolas G. M.; Sanders, Drewan S. (Elsevier, 2026)
Propulsive fuselage aircraft concepts integrate a rear-mounted propulsion system alongside under-wing turbofans, leveraging fuselage boundary layer ingestion to enhance overall aerodynamic efficiency. Despite its promise, this configuration lacks a universally accepted framework for assessing its aerodynamic benefits, motivating the development of new evaluation methodologies. This study advances a work-energy-based performance accounting framework, formulated in an absolute reference frame, to analyse the aerodynamic mechanisms responsible for energy extraction, deposition, and dissipation within the flow. Aero-propulsive performance is evaluated through flow-feature segmentation, enabling quantitative attribution of energy expenditure to distinct aerodynamic phenomena. The framework is applied to a propulsive fuselage concept, with a parametric exploration of propulsor fan diameter, exhaust configuration, and nozzle geometry. While fan diameter and pressure ratio are primary drivers of performance, exhaust and nozzle shaping exert secondary effects. Notably, improved aft-body performance is achieved through an embedded nacelle trailing edge and a slender, contoured nozzle plug, promoting smoother flow and reduced wake losses, resulting in 2%–5% additional fuel savings. The core contribution lies in the flow-feature segmentation approach, which enables a physically grounded interpretation of complex aerodynamic interactions, provides a robust basis for understanding the impact of design changes, and lays the groundwork for systematic optimisation of integrated propulsion–airframe configurations.
Keywords: 40 Engineering; 4001 Aerospace Engineering; Mechanical Engineering & Transports; 4012 Fluid mechanics and thermal engineering; Boundary layer ingestion; Computational Fluid Dynamics; Energy-based analysis; Flow feature segmentation; Propulsion–airframe integration